Seasonal variations in small mammal-landscape associations in temperate agroecosystems: a study case in Buenos Aires province, central Argentina - Gonzalez Fischer, Carlos Maria (2012)
We studied the associations between small mammal assemblages and patterns of land use and landscape structure, and their seasonal variations in temperate agroecosystems. We collected barn owl, Tyto alba, pellets from nest sites located in the Pampean region included in Buenos Aires province (36 sites in winter and 29 in summer). We used Google Earth and SAC-C imagery classification to describe land use and landscape structure around pellet collection sites. In winter, we found a significant relation between the relative abundances of small mammal species and landscape variables. Landscape accounted for 33.2 % of variance in species data.  Calomys spp. were relatively more abundant in sites with higher winter crops cover, while Akodon azarae and  Oligoryzomys flavescens increased their relative abundances in sites with more grassland cover. The commensal rodents  Musmusculus and  Rattus spp. were relatively more abundant in sites with higher urban cover, or near households and grain storage facilities. We found no significant small mammal-landscape association in summer. Our results are in agreement with previous studies showing that land use patterns may influence small mammal  assemblages. Moreover, our results also show that seasonality plays a major role modulating the intensity of  these small mammal landscape associations in temperate agroecosystems.